Grazing increased alpine grassland soil respiration rates on the Tibetan Plateau - Mao, Yahui; Du, Yangong; Chen, Kelong (Frontiers in Soil Science, 2025)
IntroductionGrazing activities were intensive in alpine grasslands and may alter the soil respiration rates across the Tibetan Plateau. However, grazed alpine grassland soil respiration rates and their underlying driving mechanisms remain unclear across the Tibetan Plateau.MethodsIn this study, we synthesized data from 38 groups to clarify the response of CO2 emission rates to different grazing intensities.ResultsThe effect size was 0.039 ± 0.051 of grazed activity on the ecosystem respiration rates, indicating that grazing increased respiration rates by 3.99%. Furthermore, effect sizes were −0.146 ± 0.209 and 0.076 ± 0.046 in alpine steppes and alpine meadows, respectively, indicating a 13.58% reduction and a 7.90% increase. The effect sizes were 0.051 ± 0.112, 0.029 ± 0.075, and 0.055 ± 0.089 in light, moderate, and high grazing intensity, respectively. Moderate grazing mitigated grassland CO2 emission rates compared with light and high grazing. Both air temperature and soil organic carbon significantly increased grassland ecosystem respiration rate, explaining 38.47% and 22.57% of variance heterogeneity.DiscussionIn addition, both future global warming and increasing soil organic carbon would increase alpine grassland CO2 emission rates on the Tibetan Plateau.